2017
DOI: 10.1039/c6gc02894b
|View full text |Cite
|
Sign up to set email alerts
|

Reduced graphene oxide: a metal-free catalyst for aerobic oxidative desulfurization

Abstract: Nanocarbons have been extensively used as metal-free alternatives to metal catalysts in many oxidative processes owing to their functional groups or defects, which have the activation ability toward oxygen molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(96 citation statements)
references
References 42 publications
4
92
0
Order By: Relevance
“…Carbon nanotubes with high graphitization degree demonstrated high catalytic activity in the oxidation of dibenzothiophene owing to their high electronic conduction [38], which provided electron transfer in the redox reaction. On the other hand, in [39] it was supposed that carbonyl groups and surface defects play an important role in the ODS process. In [38], structural, textural and surface properties of carbon nanotubes, for example, the Taunit CNTs, were shown to be essential for ODS.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes with high graphitization degree demonstrated high catalytic activity in the oxidation of dibenzothiophene owing to their high electronic conduction [38], which provided electron transfer in the redox reaction. On the other hand, in [39] it was supposed that carbonyl groups and surface defects play an important role in the ODS process. In [38], structural, textural and surface properties of carbon nanotubes, for example, the Taunit CNTs, were shown to be essential for ODS.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced graphene oxide (rGO) has recently been reported as an efficient aerobic oxidative catalystf or the ODS reaction under mild conditions. [12] The catalytic system is highlighted by superior catalytic performance, high stability,a nd broad applicability for ar ange of aromatic sulfur-containing substrates. The catalytic performance can be improved by simple gas-phase oxidation treatment of the catalyst by oxygen.…”
Section: Oxidative Desulfurization Of Fuelsmentioning
confidence: 99%
“…140 -0.51 [20] 7CNTs140 -5.90 [13] 8rGO-425 140 -7.19 [12] 9Fe 2 O 3 RT sunlight 1.77 [21] 10 GO 25 UV 38.52 [14] [a] Reactionr ates are normalized by the catalystw eight.…”
Section: Selectivecatalytic Oxidation Of H 2 Smentioning
confidence: 99%
“…Besides, the two‐dimensional metal‐free materials have aroused intense interest because of the advantages of abundant reserves and cost‐efficiency . More recently, it has been found that two‐dimensional metal‐free materials for ODS have potential applications …”
Section: Introductionmentioning
confidence: 99%